Hegemonia e resistência: imprensa, violência e cultura popular: pois este homem não é tão ruim quanto o senhor pensa - Lacerda, Alexandre Magno Gonzalez de (2009)
The following work inquires the differences between the speeches of the traditional mass media and the popular culture on the thematic of the violence and crime. From the research on the repercussion in the press and lyrics of samba of the escape and the arrest of Jose Carlos Dos Reis Encina, manager of the traffic of drugs of a devoid community of the suburb of Rio De Janeiro, we intend to identify the alignment of the press to the academic production of the positivist sociology, that results in the legitimating of the effective Law. On the other hand, we try to approach the speech of the work of Bezerra Da Silva, for its critics on the practices, rules of law and the state agencies of repression, of the lucubrations and conclusions of the critical criminology.